The Relationship between Land Use Conflicts and Land Cover Changes around Nairobi National Park - Mwendwa, G.; Kiplagat, A. K.; Ng`etich, J. (Africa Environmental Review Journal, 2022)
Although land cover and land use changes are important processes that affect the ecological integrity of conservation areas, there are still gaps on how these effects counteract to yield land use conflicts that bedevil protected areas. This study aimed at analyzing the relationship between land use conflicts and land use/land cover changes around Nairobi National Park. A mixed method research design was adopted. A survey was carried out on 331 households in Machakos and Kajiado Counties. Conflict data for the years 2008, 2010, 2012, 2014 and 2016 was obtained from KWS database. Conflict points were georeferenced using ArcGIS version 10.2.1 and plotted on their respective maps. Afterwards, supervised and unsupervised classification were employed for spatial analysis of GIS data for land cover and land use classes respectively for the years between 1984 and 2016. Land use change results highlighted a reduction and increase in various land use forms. Furthermore, land cover analysis also revealed that the percentage of built up areas has consistently been increasing yearly. The major preceding cause for conflicts is land use conversion form one form to the other which had led to high number of conflict cases being experienced.